Analysis Of Seismic Quiescence Precursors Before The M7.4 Earthquake Of 28 September 2018 In Central Sulawesi Based On Seismotectonic Spatial Distribution And Earthquake Fracture Lengths - zu, Zurahma; Syafriani; Dwiridal, Letmi; Zulhendra, Zulhendra (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The Central Sulawesi earthquake with coordinates 2°30‘S -1°50’ N and 119°0'-124°20 E magnitude 7.4 in Palu, Donggala Regency on 28 September 2018. This earthquake was a significant and destructive earthquake in Central Sulawesi. A significant earthquake is preceded by a seismic quiescence. The aim of the study was to determine when the seismic quiescence occurred and seismic activity after the earthquake alongside fracture length. The method of analysis of seismic quiescence and fracture length is z-value and Wells and Coppersmith equation. Data processed with MATLAB and Zmap were 1478 events from 1983-2023. The study area is divided into several grids with sizes of 0.1°* 0.1°. The number of earthquakes included (N = 800, 700, 600, 500, 400, 300, and 200). The z-value was calculated for each grid based on the earthquake data organized in one grid and seismic activity after earthquake. The results of the analysis of the z-value calculation in each grid show of seismic quiescence before a significant earthquake. Based on the results of the spatial distribution of z-value in Central Sulawesi, the seismic quiescence preceded the 28 September 2018 earthquake event (M 7.4) by about 21 years beginning in 1990. When cut at 2019.6, there was a decrease in seismic activity again, which indicated that an earthquake would occur, so it was thought to be a trigger factor for future earthquake precursors. While the fracture length of the 7.4 Mw earthquake of 104,232 meters shows a positive correlation between magnitude and fracture length.